Predicting the Primitive Form of Rhombohedral Silicon Carbide (9R-SiC): A Pathway toward Polytypic Heterojunctions - Yaghoubi, Alireza; Ramesh, Singh; Melinon, Patrice (American Chemical Society, 2018)
The simplest form of rhombohedral silicon carbide is unknown. Previous studies of the elusive 9R-SiC have failed to show whether this polytype is stable as a bulk material. Here, we demonstrate that when molecular bonds along the c-axis of 2H-SiC are broken under tension, miniscule levels of stacking fault could give rise to the formation of 9R polytype and hence a Type II heterojunction. 9R-SiC has a very similar microscopic and crystallographic signature to that of 3C-SiC and 15R-SiC, respectively, which explains why it has evaded detection until now. Its vibrational footprint on the other hand is quite distinct thanks to its fewer active phonon modes. Surprisingly, the indirect band gap of this polytype is slightly wider than that of 2H-SiC, despite its lower hexagonality, and is equivalent to that of GaN. Due to its unique conduction band structure, 9R-SiC may also exhibit improved electron transport properties as compared to other SiC polytypes, and therefore could be suitable for high-frequency and high-voltage applications.